Design and Implementation of a User-Centered Web-App using Open Source Platform: Indonesia Disaster Data (InDITA) - Aninda Wisaksanti Rudiastuti; Ellen Suryanegara; Ade Wirawan; Bayu Purwanto; Suzan Novtalia Gill; Yosef Prihanto; Rizka Windiastuti; Munawaroh Munawaroh (Politeknik Negeri Padang, 2020)
The availability of updated and easy access to geospatial data and information is the main thing in disaster mitigation and sustainable spatial planning. This needs to be supported by the rapid development of technology in the aspect of spreading data and spatial information via the internet. The Spatial Data Infrastructure (SDI) is realized as an implementation of spatial data distribution. SDI is an integrated mechanism to make it easier for spatial data users to access, search, share, and use spatial data and information. Built upon the background statements, the research does intend to develop a web-app which is functioned as a data repository, viewer, and also simple processing (web GIS). To design and develop a disaster geospatial online application web-app that has an integrated function (repository-web GIS) following the directions and input from user feedback becomes the fold of the research. . The importance of putting the user needs in building a web-app to be used by anyone universally is more realistic and practical. The user interface is very essential in bridging communication between users and web mapping systems. User-centred design (UCD) implemented by gathering input and feedback from users. UCD describes the process of ensuring interface success throughout the design and development of the interface. GeoNode has chosen as the platform since it is open-sourced, and commonly used for managing and publishing geospatial data. Based on respondents' assessment of the quality of content/information that important to be developed in a disaster website, it is recognized that providing reliable and up-to-date data and information (69%) and the accuracy of data and information (74%) are the most important things to develop in the InDITA application. the most important features to respondents are the spatial data display feature/map viewer (89%). The design of InDITA was built interactive and user-friendly which designed as an application that accommodates simple viewer, data repository, and web GIS functions. The interactive design emerged as the demand for app users.